2016
DOI: 10.1016/j.clinph.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonus in the critically ill: Diagnosis, management, and clinical impact

Abstract: Myoclonus is the second most common involuntary non-epileptic movement in intensive care units following tremor-like gestures. Although there are several types of myoclonus, they remain underappreciated, and their diagnostic and prognostic associations are largely ignored. This review discusses clinical, electrophysiological, neuroanatomical, and neuroimaging characteristics of different types of myoclonus in critically ill adults along with their prognostic impact and treatment options. Myoclonus is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 145 publications
(236 reference statements)
1
27
1
Order By: Relevance
“…This distinction is key, because many cases previously described as “acute” PHM were later diagnosed as being LAS once the patient awakened (Freund et al, 2016, Gupta and Caviness, 2016). Specific clinical indicators that have been studied to discriminate LAS and MSE, and to delineate subtypes of MSE include: time to onset of myoclonus after CA (Bouwes et al, 2012, Gupta and Caviness, 2016, Malhotra and Mohinder, 2012, van Zijl et al, 2016), outcomes (Bouwes et al, 2012, Elmer et al, 2016, English et al, 2009, Harper and Wilkes, 1991, Lance and Adams, 1963, Malhotra and Mohinder, 2012, Rossetti et al, 2016, Seder et al, 2015, Sutter et al, 2016, Wijdicks et al, 1994, Young et al, 1990), response to treatment (Chadwick et al, 1977, Werhahn et al, 1997, Witte et al, 1988), clinical characteristics of myoclonus (Bouwes et al, 2012, English et al, 2009, Gupta and Caviness, 2016, Hallett et al, 1977, Hallett, 2000, van Zijl et al, 2016), and neurologic exam with particular focus on the presence of coma (English et al, 2009). …”
Section: Clinical Features Of Phmmentioning
confidence: 99%
See 3 more Smart Citations
“…This distinction is key, because many cases previously described as “acute” PHM were later diagnosed as being LAS once the patient awakened (Freund et al, 2016, Gupta and Caviness, 2016). Specific clinical indicators that have been studied to discriminate LAS and MSE, and to delineate subtypes of MSE include: time to onset of myoclonus after CA (Bouwes et al, 2012, Gupta and Caviness, 2016, Malhotra and Mohinder, 2012, van Zijl et al, 2016), outcomes (Bouwes et al, 2012, Elmer et al, 2016, English et al, 2009, Harper and Wilkes, 1991, Lance and Adams, 1963, Malhotra and Mohinder, 2012, Rossetti et al, 2016, Seder et al, 2015, Sutter et al, 2016, Wijdicks et al, 1994, Young et al, 1990), response to treatment (Chadwick et al, 1977, Werhahn et al, 1997, Witte et al, 1988), clinical characteristics of myoclonus (Bouwes et al, 2012, English et al, 2009, Gupta and Caviness, 2016, Hallett et al, 1977, Hallett, 2000, van Zijl et al, 2016), and neurologic exam with particular focus on the presence of coma (English et al, 2009). …”
Section: Clinical Features Of Phmmentioning
confidence: 99%
“…Given the appearance of epileptiform activity both clinically and electroencephalographically, anti-seizure drugs (ASD) are often first line, with anesthetics used if these fail (Gupta and Caviness, 2016). Clonazepam is often used, and serotoninergic medications have also been tried (Hallett, 2000) though myoclonus in MSE is usually difficult to treat (Sutter et al, 2016). Previously it was believed that the anatomic localization of myoclonus could be made based on the response to treatment, but has not been consistently demonstrated (Chadwick et al, 1977, Werhahn et al, 1997, Witte et al, 1988).…”
Section: Clinical Features Of Phmmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies around that time also confirmed a poor prognosis in those with early PHM (11,12). Though more recent studies have reaffirmed the 0% false positive rate in determining poor outcome due to myoclonus (13)(14)(15)(16)(17)(18)(19), there have been a number of publications that demonstrate a higher false positive rate (3)(4)(5)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and have since challenged the way we view early PHM (33).…”
mentioning
confidence: 99%